Relationship of Working Period in Tobacco Industry with Cervical Precancerous - Nur Venny Ratnasari; Afnani Toyibah (Jurnal Berkala Epidemiologi, 2018)
Background: Cervical cancer prevalence ranks 7th globally and number 8th as the cause of death. Cervical cancer is ranked 2nd out of the 10 most cancers in Indonesia with an prevalence of 12,70%. Purpose: The aim of this research was to identify the relationship between females working period and the cervical precancerous lesions on female workers in “J” tobacco industry. Methods: This research was an analytical study using cross sectional design. The population of this research was female workers of "J" tobacco industry in Kepanjen Sub-District of Malang Regency in cigarette rolling and packing who had married in the age group of more than 35 years old (>35). This population consists of 147 people. Sampling technique used in this research is simple random sampling technique. The number of samples required is 39 respondents. Variables used in this research were working period and the cervical precancerous lesions. The statistical test used is fisher exact test which has purpose to know the correlation between the variables. Results: The study shows that 34 respondents has been working period at factory <10 years (87%) and 2 respondents who detected positive IVA, has been working period at factory ≥ 10 years (40%). The statistical test shows that there is a correlation between the working period and the cervical precancerous lesions (p = 0,01). The longer women work in the factory, the more likely they get the cervical precancerous lesions. Conclusion: There was a relationship between females working period and the cervical precancerous lesions.